Tinjauan Work engagement Dan Psychological Well Being Berdasarkan Jenis Kelamin Pada Pegawai Rumah Sakit Mata Medan Baru - Hanum, Farida; Dwitama, Nabila Vina; Syafrizaldi, Syafrizaldi; Hasmayni, Babby; Yuris, Evicenna (Universitas Medan Area, 2024)
This research aims to examine the differences in Work engagement and psychological well-being based on gender among employees at the Medan Baru Eye Hospital. Work engagement is a state in which an individual feels motivated in their job and is able to accept all input and support from the work environment. Meanwhile, psychological well-being is an outcome of an individual's evaluation of their ability to recognize unique potential within themselves in facing various challenges and changes in their lives. Based on the research results, it is found that the calculation of the t-test reveals differences in Work engagement between males and females. The independent sample test shows that males have a significance value of 0.003, and females have a significance value of 0.004, both of which are 0.05. Another result indicates that, according to the independent sample test, males have a significance value of 0.549, and females have a significance value of 0.521, with both values being p 0.05. This implies that there is no significant difference in psychological well-being between males and females.